2020
DOI: 10.1093/inthealth/ihaa008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Housing and Infrastructure on handwashing in Peru

Abstract: Background The metropolitan area of Lima, Peru has a third of the nation’s population living in slum dwellings that are hypothesized to contribute to inefficient household hygienic practices. The purpose of this study was to quantitatively assess which living conditions have the greatest impact on handwashing practices. Methods A cross-sectional epidemiological design of participants ≥16 y of age from San Juan de Miraflores, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A study conducted in the Peruvian territory reported that the enterobacterium Escherichia coli was found in the water for human consumption in one out of four households, indicating the presence of a pathogen that causes diarrheal diseases in the population ( 35 ). In addition, it has been reported that other limitations include inadequate practice of handwashing (due to a greater number of children in the home) ( 36 ) and climatic changes (especially an increase in environmental temperature) perceived in Peru ( 37 ), thereby producing an increase in the prevalence of childhood diarrhea. In this regard, government institutions should redouble their efforts to ensure compliance with Sustainable Development Goal 6, which seeks to improve access to and quality of water in the population and, consequently, to reduce the burden of disease due to childhood diarrhea and the costs of this disease to the health system ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the Peruvian territory reported that the enterobacterium Escherichia coli was found in the water for human consumption in one out of four households, indicating the presence of a pathogen that causes diarrheal diseases in the population ( 35 ). In addition, it has been reported that other limitations include inadequate practice of handwashing (due to a greater number of children in the home) ( 36 ) and climatic changes (especially an increase in environmental temperature) perceived in Peru ( 37 ), thereby producing an increase in the prevalence of childhood diarrhea. In this regard, government institutions should redouble their efforts to ensure compliance with Sustainable Development Goal 6, which seeks to improve access to and quality of water in the population and, consequently, to reduce the burden of disease due to childhood diarrhea and the costs of this disease to the health system ( 5 ).…”
Section: Discussionmentioning
confidence: 99%